Tourism Business "Staycation" at D'emmerick Salib Putih Hotel Salatiga in the Aftermath of the Covid 19 Pandemic in the Perspective of Resilience - Irene Grace Madah; Jannet Gloria M Kahiking; Lidya G Imanuela Wattimury; Yanti Florida Silopo; Sutarto Wijono (Journal of Social Research, 2023)
This study aims to find out the extent of the resilience of the Parawisata Business "Staycation" D'Emmerick White Cross Salatiga Hotel in the Post-Covid 19 Pandemic. The theory used is the theory of resilience. Resilience itself is the ability to survive, adapt to something that is stressful, able to overcome and go through and be able to recover from a downturn. This research uses a type of qualitative descriptive method research, where the data collection technique used is an interview with an entrepreneur in this case the D'emmerick Hotel HRD, observation is carried out in the form of overall hotel observations at the research location and documentation in the form of photo documents, and sound recordings, which aims to strengthen the results of interviews and observations so that the data received is really valid. The results of the study found that the results showed that d'Emmerivk Hotel has characteristics that describe resilience based on seven aspects according to Reivich and Shatte. First, Emotional Regulation is able to manage and regulate existing emotions so that the business continues to run even under the pressure of a crisis. Second, Optimism (Optimism), is the positive side of the cooperation that is built so that even though it has decreased income. Third, Self-Efficacy is the confidence that they are able to survive in the midst of a pandemic crisis. This belief is what keeps hotels operating in the midst of a pandemic, Fourth, Causal Analysis, conducts an analysis to see the strengths, weaknesses, opportunities, and threats of the crisis at hand. Fifth, Empathy (Empathy), some laid-off employees are then called in for rehires. Sixth, Achievement (Reaching Out), received the best hotel certificate as an award for d'Emmerick hotel of the Ministry of Tourism creative economy. Thus the park tourism business d'Emmerick Hotel has the resilience of being able to improve itself and bounce back from difficult situations and be able to adjust flexibly to continue operating.